Blurred Promises: Ethical Consequences of Fine Print Policies in Insurance - Kvalnes, Øyvind (2011)
The insurance industry’s practice of producing comprehensive insurance policies can have unforeseen and negative ethical consequences. Insurance policies express promises from the insurer to the insured, to the effect that the insurer should be trusted to appropriately assist the insured in case of accident. The relation is seriously undermined when the content of the promise is blurred, containing clauses and condition which are ambiguous or hidden in fine print. This paper contains an investigation of (1) the sources of the fine print policy practice, (2) its immediate effects on the degree to which the policies are understandable to the insured, (3) the ethical consequences that can follow from blurring the true content of the insurer’s promise to the insured and (4) the measures insurers can take in order to develop a more constructive ethical relationship with its customers.
Keywords: True Content; Plain Language; Insurance Industry; Insurance Policy; Moral Hazard